Distribution and abundance of Rincalanus Nasutus (Giesbrecht 1888) (Calanoida, Copoda) in the upwelling region of Northern Zamboanga Peninsula - Sillo, Kayla Gayle (2016.)
The distribution and abundance of Rhincalanus nasutus was investigated in the Northern Zamboanga Peninsula during a northeast monsoon-driven coastal upwelling. Three depth strata (0-65m, 65-135m, 135-200m) at three stations were sampled using a paired NORPAC net with 100- and 200- µm meshed nets with opening and closing mechanism. Samples used for this study were obtained form the 200-µm net. The overall mean density of R. nasustus across all depths of all three stations was 31.9 individuals m-3. There was a significant difference in the densities of R. Nasutus in the three stations with the highest density obtained form the offshore station, station 6 (85.3 indivs m-3).. However, no significant difference was obtained in the horizontal distribution for the three stations. The inshore and the offshore stations were also found to be dominated by larger sized R. nasutus ranging form 2.6-4.8mm for the inshore and 1.7-4.3mm in the offshore station. The station in the strongest upwelling region showed an extreme size distribution of 1.2-4.4mm with smaller individuals concentrated in the upper layer (0-65m), and larger ones in the lower layer (135-200m) with a combination of large and small individuals in the middle layer (135-200m). In all depths of all stations, female R. nasutus dominated. Significant difference in the sex ratio was obtained in station 2(χ2= 10.9, p=0.001) and station 6(χ2= 5.71, p=0.0169) but not in station 4(χ2= 3.13, p= 0.0771). The reproductive behaviour of R. nasutus females may have contributed to the spatial distribution of the species as well as their vertical distribution in addition to the Ekman transport, causing nutrient distribution variation in the area. The abundance of sardines and other zooplankton-feedong species in the area may be another factor affecting the distribution and abundance of R. nasutus in Northern Zamboanga Peninsula.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Rhincalamus Nasutus; Northern Zamboanga Peninsula